Description of two cases of follicular dendritic cell sarcoma, including next-generation sequencing analysis - Yuchen Jing; Hua Ye; Shuai Luo; Jinjing Wang (Diagnostic Pathology)
Abstract Follicular dendritic cell sarcoma (FDCS), an infrequent malignancy, poses diagnostic challenges due to its nonspecific clinical presentations and propensity for recurrence and metastasis, particularly when assessed through imaging modalities. Accurate diagnosis relies heavily on pathological morphology and immunohistochemical analysis. This study examines two FDCS cases from the Affiliated Hospital of Zunyi Medical University. Next-generation sequencing (NGS) identified three gene rearrangements—HFM1::BIRC3, ELF4::AIFM1, and DIP2B::WIF1 —in one case, while no genetic alterations were detected in the other. The report explores clinicopathological characteristics, molecular genetics, differential diagnosis, therapeutic approaches, and prognosis to enhance diagnostic and pathological understanding of FDCS in medical practice.